The clinical significance of microRNA-409 in pancreatic carcinoma and associated tumor cellular functions. Issue 1 (1st January 2021) - Long, Kui; Zeng, Qingbin; Dong, Wenzhi
ABSTRACT: In recent years, the increasing incidence of pancreatic carcinoma (PC) patients has become one of the hot issues in the world. microRNAs (miRNAs) can act as oncogenes or tumor suppressor genes and have unpredictable effects on tumors, thus affecting the prognosis and survival of cancer patients. In this paper, we mainly studied the role of microRNA (miR)-409 in PC. The expression levels of miR-409 were analyzed by qRT-PCR. Kaplan-Meier curve and Cox regression were used to analyze the relationship between miR-409 and patient prognosis. The effects of miR-409 on the abilities of proliferation, migration and invasion were detected by CCK-8 and Transwell. The expression levels of miR-409 were down-regulated in PC, compared with normal controls. The prognosis of patients with low miR-409 expression is significantly poor in comparison with those with high expression. The down-regulation of miR-409 was conducive to the proliferation, migration and invasion of PC cells. miR-409 is a tumor suppressor of PC, the clinical significance of miR-409 in pancreatic cancer and related tumor cell function was clarified. Graphical Abstract: uf0001